Cellular and molecular level host-pathogen interactions in Francisella tularensis: A microbial gene network study. (February 2022) - Miryala, Sravan Kumar; Ramaiah, Sudha
Abstract: Due to the high infectivity and fatal effect on human population, Francisella tularensis (F. tularensis) is classified as a potential biological warfare agent. The interaction between host and pathogen behind the successful establishment of F. tularensis infection within the human host is largely unknown. In our present work, we have studied the molecular level interactions between the host cellular components and F. tularensis genes to understand the interplay between the host and pathogen. Interestingly, we have identified the pathways associated with the pathogen offensive strategies that help in invasion of host defensive systems. The F. tularensis genes purL, katG, proS, rpoB and fusA have displayed high number of interactions with the host genes and thus play a crucial role in vital pathogen pathways. The pathways identified were involved in adaptation to different stress conditions within the host and might be crucial for designing new therapeutic interventions against tularemia. Graphical Abstract: A total number of 33 whole genome sequences available for various F. tularensis strains were downloaded from NCBI database. The phylogenetic tree was constructed using ParSNP tool and visualized using iTOL tool. The representative strain F. tularensis SUH4 was highlighted in yellow color. (A) Phylogenetic tree in rooted tree layout, and (B) Circular tree view of phylogenetic tree. ga1 Highlights: Phylogenetic tree of 33 whole genome sequences of Francisella strains constructed. Gene interaction network between 377 host and 237 pathogen genes was constructed. Clustering analysis of gene networks resulted densely inter connected gene clusters. FEA has resulted with key pathways which play critical role in host and pathogen. Important pathogen genes were identified and reported as new potential drug targets.